2022
DOI: 10.2460/ajvr.21.10.0169
|View full text |Cite
|
Sign up to set email alerts
|

Healing time of experimentally induced distal limb wounds in horses is not reduced by local injection of equine-origin liquid amnion allograft

Abstract: OBJECTIVE To assess the efficacy of an equine-origin liquid amnion allograft (ELAA) derived from both amniotic fluid and amniotic membrane on the healing time of experimentally induced distal limb wounds in horses. ANIMALS 8 adult horses. PROCEDURES On day 0, horses were anesthetized and a 2.5 X 2.5-cm, full-thickness skin wound was created on the dorsal aspect of each metacarpus and bandaged. On day 9, wound margins were injected with ELAA (treatment) or 0.9% NaCl (control). Bandages were changed at speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Allografts involve using skin from another horse, which carries a higher risk of host site rejection. Recently, the efficacy of an injectable allogeneic amnion product has been of interest with regard to wound healing, although one study indicated that there is no significant difference in experimental wound model healing compared to controls (Duddy et al., 2022). Finally, use of xenografts, such as porcine or fish skin, that do not integrate into the recipient animal wound bed but are instead used as biological bandages have been described.…”
Section: Skin Graft Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Allografts involve using skin from another horse, which carries a higher risk of host site rejection. Recently, the efficacy of an injectable allogeneic amnion product has been of interest with regard to wound healing, although one study indicated that there is no significant difference in experimental wound model healing compared to controls (Duddy et al., 2022). Finally, use of xenografts, such as porcine or fish skin, that do not integrate into the recipient animal wound bed but are instead used as biological bandages have been described.…”
Section: Skin Graft Classificationmentioning
confidence: 99%
“…Allografts involve using skin from another horse, which carries a higher risk of host site rejection. Recently, the efficacy of an injectable allogeneic amnion product has been of interest with regard to wound healing, although one study indicated that there is no significant difference in experimental wound model healing compared to controls (Duddy et al, 2022).…”
mentioning
confidence: 99%
“…In a retrospective study including 500 injured horses and ponies, only 26% of the wounds in horses were successfully treated with primary closure [7]. Horses often live in highly contaminated environments and secondary intention wound healing is usually predominant [8][9][10]. However, wounds on the limbs can lead to complications and additional treatment is often required [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable interest in developing novel approaches to improve the healing rate of lower limb wounds in horses, 1 with, histori-cally, a strong focus on optimising the wound bed microclimate. 2 The effect of treatment has been investigated in experimental models of surgically created wounds 2,3 and in clinical trials of naturally occurring wounds 4 ; however, such studies have focused heavily on wound healing without considering analgesia.…”
Section: Introductionmentioning
confidence: 99%